Tuition Fee Regulation, Unit Cost, Cost Recovery, and Financial Performance in Public Higher Education: A Comparative Study of Nigeria, the UK, and the USA - Christopher Enyioma Alozie (Transpublika Publisher, 2026)
Backgrounds: Regulated tuition fees fall below economic costs, widening the gap between revenue and unit cost. This deepens reliance on state subsidies and threatens the financial sustainability of public universities. Objectives: This study compares financial sustainability in public universities across Nigeria, the UK, and the USA using financial performance indicators. It tests five hypotheses on cost absorption, covering unit cost, tuition revenue, cost recovery, funding subsidies, and efficiency across 12 institutions. Methodology: This study compares financial sustainability across 12 public universities in Nigeria, the UK, and the USA using performance indicators. It tests five hypotheses on cost absorption: unit cost, tuition revenue, cost recovery, subsidies, and efficiency. Findings: Result show statistically significant differences in unit cost, tuition revenue, subsidy, and sustainability ratios across countries. Cost recovery ratios range from 16% for Nigeria, 28% for the UK and 39% in USA, indicating substantial subsidies. It identified emerging proximity in Nigeria and UK’s public universities’ operating margins and net asset returns despite different cost/tuition levels which has been underexplored and reported in the existing HEIs financial evaluation studies. Similarly, it established that Nigeria’s public sector HEIs do not fully capture cost-of-service delivery and make supplementary disclosure(s) cost under-recovery in their financial statements as expected in low-cost, high subvention cluster(s). Conclusions: These results provide cross-national metrics for higher education finance and show how revenue constraints affect accounting. They reveal similar operating margins and net asset returns between Nigeria and the UK. Nigerian public universities should disclose cost under-recovery in financial statements.